An X-Ray Study Of The Gold-Iron Alloys - Eric Jette (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
THE alloys of gold and iron were investigated in 1907 by Isaac and Tammann,1 who determined the thermal diagram for the entire system by thermal analysis and microscopic examination. They also reviewed the previous literature. Since that time the present authors have been able to find only two additional references. Guertler and Schulze2 examined the electrical resistance of iron alloys containing up to 40 per cent by weight of gold between 0° and 200° C.; the alloys were in the form of wires. The main result of this work was to confirm the solid solubility limit found by Isaac and Tammann; namely, about 20 per cent Au. More recently, Shih3 has examined the magnetic properties of gold alloys containing up to 10 weight per cent iron and particularly the range below 5 per cent. The alloys in the lower range were found to be paramagnetic; the 10 per cent alloy was ferromagnetic. The present investigation was undertaken to determine the solid solubility limits at various temperatures, particularly below the a-y transformation point of iron, since these solubilities are of some impor-tance in connection with the working of the alloys in the manufacture of certain "grey" and "blue" golds.